Belajar Bahasa Inggris Lewat Permainan Tradisional: Integrasi Budaya Lokal dalam Pembelajaran Kosakata - Latuheru, Henry; Abdullah, Ayu Aprilya Sari (Abdimas Indonesian Journal, 2025)
Traditional games offer valuable potential to support English vocabulary learning in ways that are interactive, culturally relevant, and enjoyable. This community service initiative aimed to introduce and model the use of local games—specifically Snakes and Ladders and Vocabulary Domino—as tools to enrich English language learning among students. The program targeted English teachers and pre-service teachers in Ambon, with 40 participants attending a two-hour workshop. The methods combined short lectures with hands-on practice, allowing participants to experience the adapted games directly. The content of the games focused on daily activity vocabulary and was presented in both English and Indonesian. A post-workshop questionnaire indicated that participants found the approach engaging, practical, and applicable to their teaching contexts. Many expressed interests in developing similar games based on local wisdom. These findings support the idea that integrating game-based learning with local content can promote contextualized teaching, enhance learner motivation, and preserve cultural identity in the classroom.